IMPLEMENTASI METODE PEMBELAJARAN DRILL BERBASIS PENGGUNAAN SOFTWARE CUTVIEWER PADA MATA PELAJARAN CNC TU-3A - Putra, Ananda Yhuto Wibisono (Jurnal Nosel, 2015)
The objective of this research is to improve skill and conceptual understanding on programing CNC TU-3A for twelfth grade level in SMK N 5 Surakarta by implementation of the drill learning method with CutViewer Software based. This research was belong to classroom action research. This research was implemented in two cycles, each cycle was composed of four stages, there was planning stage, action stage, observation and reflection. Every cycle is carried out in two meetings. The subjects of this research were twelfth grade level in SMK N 5 Surakarta. The data were collected from teacher and students. The techniques of data collection were observation, interview, and learning achievement test. The method of data validity were Expert Judgement and Construct validity. The resulting data were analyzed as quantitative descriptive and comparative descriptive. The result of this research showed that the implementation of the Drill learning method of CutViewer Software could improved skill and conceptual understanding of student on CNC TU-3A programing. At initial condition, the skill of the student was 45,31%, meanwhile the conceptual understanding of students was 35,23%, and the average score of learning result was 64,58. After the action of the first cycle, student?s skills increased to 73,44% and the conceptual understanding become 70,17% with the average score of learning result was 84,67. At the action of the second cycle, skill of students become 88,75% and the conceptual understanding increased to 89,77%, and the final average score of learning result was 92,52. The conclusion of this research is the implementation of the Drill learning method of CutViewer Software based could increase the skill and conceptual understanding of students on CNC lesson especially on CNC TU-3A programming.